Formulation Of Instant Functional Collagen Drink With Date Seeds Coffee (Phoenix dactylifera) And Spices (Ginger, Cinnamon, Cardamom, Clove) Using The D-Optimal Mixture Design Method - Mutia Hanifa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The functional food trend has grown rapidly since the Covid-19 pandemic, including products made from natural ingredients like herbal collagen drinks. This research aims to develop an optimal collagen drink formulation by adding date seed coffee with ginger, cinnamon, cardamom, and cloves as antioxidants to optimize collagen function.Optimization was carried out using the Design Expert-13 device with the optimization response of antioxidant activity (mg TE/100g) and water content (%). The results showed that the optimal formulation consisted ofdate seed coffee 35.57%; hydrolyzed collagen 25%; and spice mixture (ginger, cinnamon, cardamom, cloves) of 39.432% with a desirability value of 0.741.The optimal product was then instantiated using the spray drying method and compared with commercial products without instantiation and collagen addition.The optimal product has an IC50 antioxidant activity of 743.86 ppm and total phenols of 187.23 mg GAE/100g), with a water content of 3.35%, hygroscopicity of 7.76%, bulk density of 0.488 g/mL, and a dissolution time of 23.32 seconds. The results of the hedonic test on the optimal sample as a whole from 100 panelists were â€œrather likeâ€ to â€œlikeâ€ with an average value of 3.17 with the most preferred attributes being the consistency and aroma of spices.